(untitled) (World Bulletin of Social Sciences, 2023)
The research aims to test the influence relationship of variables of current study, as strategic improvisation(SI) is an independent variable through its dimensions in organizational creativity(OC) as an approved variable for a sample of leaders in the Iraqi Tourism Authority, as (60) questionnaires were distributed distributed to (general managers, assistant general manager, heads Departments, people’s officials), especially since the variables of study have received increasing attention at present time as they are among modern topics in field of strategic management, these variables have interacted to form general framework for the research, the main and sub-hypotheses have emanated from them in order to achieve the aforementioned research objectives